PERANCANGAN APLIKASI MOBILE SEBAGAI MEDIA PROMOSI TEMPAT KOST DAN FASISILTAS PENDUKUNG BERBASIS ANDROID - Tio Rahmayuda; Denny Kurniadi (Universitas Negeri Padang, 2019)
Boarding houses has its own problems in finding. The problems are boarding house location, price, facilities, surrounding environment and time to gather about boarding houses information. Landlords of boarding house also have its own problems, like disseminate information about the boarding houses is limited. Mobile application of boarding houses and support facilities is built to solve the problem in finding suitable boarding houses and also to inform the others about the boarding houses. The method used is the client-server based waterfall model. Application server side’s use the PHP programming language (PHP Hypertext Preprocessor) and web services Json and MYSQL for Database Management Systems (DBMS). Application client side’s use the java programming language and java script that can run on the android platform. The design application of boarding houses and support facilities is based android to generate three applications which are one server and two application client. The first client application has function to search information of boarding houses. The second client application is used by landlord in marketing their boarding houses.Keywords: Android, Json, Client-server,MYSQL, Boarding Houses.